A modified precise integration method for transient dynamic analysis in structural systems with multiple damping models. (1st January 2018) - Ding, Zhe; Li, Li; Hu, Yujin
Highlights: A modified precise integration method for viscoelastic damping system is proposed. The method is applicable to systems with multiple damping models. An extended state-space scheme is developed based on a general damping model. The stability and accuracy of the method are investigated. Three examples are given to show the accuracy and efficiency of the method. Abstract: Sophisticated engineering systems are usually assembled by subcomponents with significantly different levels of energy dissipation. Therefore, these damping systems often contain multiple damping models and lead to great difficulties in analyzing. This paper aims at developing a time integration method for structural systems with multiple damping models. The dynamical system is first represented by a generally damped model. Based on this, a new extended state-space method for the damped system is derived. A modified precise integration method with Gauss-Legendre quadrature is then proposed. The numerical stability and accuracy of the proposed integration method are discussed in detail. It is verified that the method is conditionally stable and has inherent algorithmic damping, period error and amplitude decay. Numerical examples are provided to assess the performance of the proposed method compared with other methods. It is demonstrated that the method is more accurate than other methods with rather good efficiency and the stable condition is easy to be satisfied in practice.